Factors of E-wallet adoption among generation Z - Li, Yi Huan; Choo, Jia Yi; Lim, Jia Xuan; Wong, Chin Yee (2020)
This research topic study on factors of E-wallet adoption among generation Z in UTAR, Kampar, there will be 6 independent variables, convenience, budgeting, security, rewards perceived usefulness and perceived ease of use. In this research, we will investigate the relationship between the variable and adoption of E-wallet among generation Z in UTAR, Kampar. Statistical Package for the Social Sciences (SPSS) has been applied to perform reliability tests, inferential analysis and scale measurement that explains the hypothesis developed.